Accounting for the genetic load in assisted reproductive technology. Issue 5 (25th May 2022) - van Oosterhout, Cock; Marcu, Daniel; Immler, Simone
Abstract: The genetic load in the human genome has important ramifications for assisted reproductive technology (ART), human reproduction and fertility more generally. Here, we discuss these topics in the light of evolutionary genetic theory, the technological revolution in ART and the advances in the fields of genomics and bioinformatics.